TINJAUAN HUKUM ATAS KEMATIAN MAHASISWA PADA KEGIATAN PENDIDIKAN DAN LATIHAN DASAR (DIKLATSAR) RESIMEN MAHASISWA (MENWA) - Husnulwati, Sri; Yanuarsi, Susi (Solusi, 2022)
The Student Regiment is an organization that serves as a forum to meet students' needs for organizational skills. But if in its implementation this organization performs actions such as persecution, it is necessary to conduct an evaluation related to the existence of this organization. This paper aims to find out how the legal review of the death of students during menwa training. The research method used in this study is a normative method of law. The results of this study are, (a) Violations that refer to the basic rules of the organization can be subject to actions in the form of sanctions that lead to the revocation of permits by the Rectorate, (b) If in the implementation of activities such as training there is persecution leading to death then the organizing committee can be subject to legal action referring to Article 351 paragraph (1) jo. paragraph (3) of the Criminal Code (Criminal Code).